2015
DOI: 10.1016/j.toxrep.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A survey of poison center knowledge and utilization among urban and rural residents of Arizona

Abstract: BackgroundPoison control centers (PCCs) hold great potential for saving health care resources particularly by preventing unnecessary medical evaluations. We developed a survey to better identify the needs and experiences of our service community. We hope to use these data to improve PCC outreach education and overall use of our services.MethodA written questionnaire was developed in English and then translated into Spanish. Subjects agreeing to participate were then asked two verbal questions in English: are y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…There are major barriers in place that make it difficult to tie specific exposures of pesticides to specific harms, particularly to BIPOC communities and those living in poverty. Poison Control Center utilization is known to be much lower in BIPOC and low-income populations, making comparisons between different racial, ethnic and income demographics very difficult [ 64 66 ]. Correctly diagnosing illness from acute pesticide harm requires the harmed individual to have access to, and seek, medical treatment, which often doesn’t happen [ 67 ].…”
Section: How Disproportionate Pesticide Impacts Are Realizedmentioning
confidence: 99%
See 1 more Smart Citation
“…There are major barriers in place that make it difficult to tie specific exposures of pesticides to specific harms, particularly to BIPOC communities and those living in poverty. Poison Control Center utilization is known to be much lower in BIPOC and low-income populations, making comparisons between different racial, ethnic and income demographics very difficult [ 64 66 ]. Correctly diagnosing illness from acute pesticide harm requires the harmed individual to have access to, and seek, medical treatment, which often doesn’t happen [ 67 ].…”
Section: How Disproportionate Pesticide Impacts Are Realizedmentioning
confidence: 99%
“…The result is a vast underestimate of the true scope of harm to this largely Latinx community. And because non-occupational injuries from pesticides are often compiled solely from reports to Poison Control Centers – utilization of which is known to be much lower for BIPOC and people of lower socioeconomic status [ 64 66 ] – a systemic issue exists with the underlying data that the program is built on.…”
Section: How Disproportionate Pesticide Impacts Are Currently Perpetu...mentioning
confidence: 99%
“…The logistic regression models found that for both time periods, percent of black or African American population was significantly associated with unintentional pesticide-related poison center exposures in children and adolescents. Existing literature has found that areas with higher percent black or African American populations have lower poison center utilization rates [ 12 , 13 , 26 ]. Lower poison center utilization may explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Low PC penetrance is associated with increased healthcare utilization, particularly in children. 5,8 Variations in penetrance have been attributed to seasonality, 6 changing pediatric population proportions, 9 limited awareness of PC services, 10 and suspicion regarding PC cost and safety of personal information. 11 Social determinants of PC penetrance are less well-defined, although several racial (Black and Native American) and linguistic (low English proficiency and native Spanish-speaking) characteristics are associated with lower PC utilization when compared to White and Englishspeaking populations.…”
Section: How Does This Improve Population Health? Statistical Analysementioning
confidence: 99%
“…11 Social determinants of PC penetrance are less well-defined, although several racial (Black and Native American) and linguistic (low English proficiency and native Spanish-speaking) characteristics are associated with lower PC utilization when compared to White and Englishspeaking populations. 5,10,12,13 The use of penetrance has been disputed over time, largely due to a perceived limited efficacy in assessing both PC efforts and outcomes. 9 Although the AAPCC discontinued its use of penetrance as one of multiple methods to ascribe efficacy to individual PC outreach and promotion efforts in 2001, it was done prior to the advent of easily accessible, geospatial mapping tools to provide a more refined data than at a county level, suggesting that penetrance may once again serve a purpose in identifying areas in which PCs are underused.…”
Section: How Does This Improve Population Health? Statistical Analysementioning
confidence: 99%